Pengaruh Kualitas Produk, Desain Produk, Dan Fitur Produk Terhadap Niat Beli Sepatu Sneakers Bata (Studi pada calon konsumen sepatu sneakers Bata) - Dewa, Reno Pramuda; Untarini, Nindria (Jurnal Ilmiah Wahana Pendidikan, 2023)
With the development of the shoe industry, sneakers are the type of shoe most liked by young people. The need for shoes that are stylish, comfortable and in accordance with the latest trends is increasingly dominant, so they tend to be more interested in sneakers. This is evidenced by the increasing interest in sneakers every year. This study aims to determine the effect of product quality, product design, and product features on the purchase intention of Bata Sneakers. The type of data used is quantitative data sourced from primary data through online questionnaire filling. The population in this study are people who know Bata sneakers and plan to buy them in the near future, where the population in this study is infinite, meaning the population is unknown. The sampling technique used in this study was non-probability sampling using a purposive sampling method. Data were analyzed using multiple linear regression and calculated using IBM SPSS 26. The results showed that product quality and product design had a significant and positive effect on purchase intention. Meanwhile, product features have no significant effect on purchase intention. Bata is expected to continue to create and offer sneakers with varied designs following current trends, so that the expectations and needs of potential customers can be met and gain their trust and attention.